The Effect of Modifiers on the Strength and Impact Toughness of Carbon Fiber Reinforced Plastics - Laura Mustafa; Marat Ismailov; Indira Tashmukhanbetova; Ilyas Ablakatov; Venera Zhumakanova (Journal of Multidisciplinary Applied Natural Science, 2025)
This study utilized epoxy resin, three types of fabric (carbon fiber, glass fiber, and Kevlar), and two plasticizers – tricresyl phosphate (TCP) and oleic acid (OA) – to enhance the impact toughness of carbon fiber-reinforced plastics (CFRP). The polymer matrix used in the experiments was a hot-cured epoxy compound "Etal Inject-T" consisting of two components: A – epoxy resin and B – hardener, in a mass ratio of 100:49.9. For the fabrication of CFRP plates, both manual and vacuum molding techniques were employed. Combined reinforcement of carbon fiber was achieved using one of two types of fabrics: Ortex 360 glass fiber or Kevlar. Accordingly, two compositions were prepared for the experiments: carbon fiber/glass fiber and carbon fiber/Kevlar. Layer stacking in each composition was performed at ratios of 10:10 and 14:6, consisting of 20 layers in total. The greatest strengthening effect for CFRP in the case of carbon fiber/glass fiber was observed with a layer ratio of 14:6 and matrix modification using 10% TCP plasticizer. The strength of the CFRP increased from 425 to 451 MPa, and the impact toughness (α) improved from 192 to 280 kJ/m². A key feature of this technology is the achievement of high-performance dual-purpose CFRP. This enables the reduction of CFRP structures in aerospace applications by 3 to 5 times, while simultaneously enhancing resistance to impact loads.